La rueda de la gestión de audiencias - Pastor, Lluís (Estudios sobre el Mensaje Periodístico, 2007)
The journalist has been trained to manage information. The journalist searches for (or, more usually, is provided with) information, selects it, contrasts it and explains it to his/her audience for them to understand. It is possible for the audience to understand it and, if it is of their interest, comment on it. Journalism is information management. I suggest the journalist to have eyes wide open to another entity which has been his/her companion for a long time but which has only been made evident thanks to the electronic media: the audience. The journalist must not only be contented himself/herself with being an information manager, he also has to take on the management of his/her audience. If the audience is part of the journalistic product, the journalist must be, as well, in charge of its management. The management of the audiences facilitates, in one hand, the fact that the public participates, and on the other hand, it orientates the contributions towards the improvement of the journalistic product and of the public’s relation with the media. The management wheel of audiences is made up of six stages.